EXPLORING THE IMPACT OF TASK-BASED LANGUAGE TEACHING (TBLT) APPROACH ON ORAL PROFICIENCY IN ENGLISH AS A FOREIGN LANGUAGE (EFL) LEARNERS - Mefta Mapiro; Zavera Dwi Permata (PT. Intelek Cendikiawan Nusantara, 2024)
Task-Based Language Teaching (TBLT) has gained prominence in language education for its effectiveness in enhancing speaking proficiency among English as a Foreign Language (EFL) learners. Unlike traditional methods that focus on isolated grammar and vocabulary instruction, TBLT emphasizes the use of meaningful tasks that mirror real-life communication. This study employs a quasi-experimental design with pre-test and post-test measures to evaluate the effectiveness of TBLT in improving EFL learners' speaking skills. Participants are divided into an experimental group receiving TBLT instruction and a control group receiving traditional instruction. Data is collected through audio recordings of speaking tasks, questionnaires, and interviews to assess aspects such as fluency, accuracy, and complexity. Results indicate that TBLT significantly enhances speaking proficiency by providing authentic communication practice, thereby addressing common challenges such as limited vocabulary, incorrect pronunciation, and lack of confidence. The findings underscore the advantages of TBLT in fostering communicative competence, increasing learner confidence, and creating a supportive learning environment. The study supports the assertion that TBLT is a more effective and engaging approach compared to traditional methods, offering valuable insights into its application in language education